2018
DOI: 10.1051/0004-6361/201832989
|View full text |Cite
|
Sign up to set email alerts
|

The XXL Survey

Abstract: Context. The luminosity function (LF) is a powerful statistical tool used to describe galaxies and learn about their evolution. In particular, the LFs of galaxies inside clusters allow us to better understand how galaxies evolve in these dense environments. Knowledge of the LFs of galaxies in clusters is also crucial for clusters studies in the optical and near-infrared (NIR) as they encode, along with their density profiles, most of their observational properties. However, no consensus has been reached yet ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
(110 reference statements)
6
12
0
Order By: Relevance
“…As discussed in Section 5.1, we assume a single Schechter luminosity function to estimate the light residual from faint unmasked cluster galaxies. As with the parameters of the Schechter function, given recent measurement uncertainties of the cluster galaxy luminosity function (e.g., Lan et al 2016;Ricci et al 2018), we find that varying the faint-end slope parameter by ±0.2 or the characteristic magnitude parameter by ±0.5 mag changes the estimated fraction of residual light by ∼ 1%.…”
Section: Psf Effectsupporting
confidence: 75%
“…As discussed in Section 5.1, we assume a single Schechter luminosity function to estimate the light residual from faint unmasked cluster galaxies. As with the parameters of the Schechter function, given recent measurement uncertainties of the cluster galaxy luminosity function (e.g., Lan et al 2016;Ricci et al 2018), we find that varying the faint-end slope parameter by ±0.2 or the characteristic magnitude parameter by ±0.5 mag changes the estimated fraction of residual light by ∼ 1%.…”
Section: Psf Effectsupporting
confidence: 75%
“…Jones & Forman 1999). They appear as diffuse extended sources (Abell 1958;Bahcall & Cen 1993;Böhringer et al 2004;Oguri et al 2018;Ridl et al 2017;Ricci et al 2018;Wen & Han 2018;Andreon et al 2019;Gozaliasl et al 2019), with galaxy overdensities extending out to over 10 Mpc (Trevisan et al 2017). Galaxies within halos may have their properties affected by encounters with the hot gas (e.g., Popesso et al 2015;Lotz et al 2019;Owers et al 2019).…”
mentioning
confidence: 99%
“…Evolutive correction is not applied since we want to investigate this. In this work, the stacking of the LF is done as proposed by Garilli et al (1999), since the Colless (1989) method was shown in Ricci et al (2018) to assign more weight to the poor clusters. Following these prescriptions, the stacked LF is built by summing the cluster galaxies in absolute magnitude bins and scaling it by the richness of their parent clusters as follows:…”
Section: Stacked Lfmentioning
confidence: 99%